Hukum dan keadilan sosial tantangan dan peluang dalam menghadapi perubahan sosial dan teknologi - mardani, muhamad (Maliki Interdisciplinary Journal, 2025)
Law and justice are two fundamental concepts that are closely interrelated in the legal system, functioning as guidelines for human behavior and the achievement of an ideal social order. In Indonesia, the realization of justice, which is based on Pancasila, faces various complex challenges. The rapid development of the digital era brings new challenges to the law, such as issues of privacy, intellectual property, cybercrime and sharing economy regulations, which demand rapid and relevant adaptation. Law enforcement in Indonesia itself is still shadowed by various obstacles, including the legalistic-formalistic paradigm, corruption, and the need for effective legal protection for citizens. Legal philosophy offers a framework for understanding and addressing these challenges, encouraging a progressive approach that prioritizes substantive justice. Apart from that, understanding inclusive gender concepts from a legal and justice perspective, as well as internalizing the values of religious moderation, are crucial in building social justice. Therefore, comprehensive legal adjustments, taking into account ethical values and public participation, are essential to respond to the dynamics of social and technological change, in order to create a just and harmonious society. Law and justice are two fundamental concepts that are closely related to each other in the legal system. In Indonesia, the realization of justice faces complex challenges, including the development of the digital era which brings issues of privacy, intellectual property and cyber crime. Law enforcement in Indonesia still faces obstacles, such as the legalistic-formalistic paradigm and corruption.